Persepsi Pegawai Terhadap Gaya Kepemimpinan Gubernur Sumatra Barat - Melia, Mutiara; Syamsir, Syamsir; Alfi Utami, Maulidya; Brasco, Randa; Thariq, Muhammad (Jurnal Humaniora, Ekonomi Syariah dan Muamalah, 2023)
This study is useful for knowing employee perceptions of the leadership style of the Governor of West Sumatra. The governor as a regional leader has an important role in managing and directing the running of regional government in West Sumatra. An effective leadership style can have a positive impact on employee performance and organizational efficiency. This study uses a qualitative approach by conducting in-depth interviews with a number of employees within the West Sumatra provincial government. The results of this study indicate the existence of the leadership style of the Governor of West Sumatra, namely Laissez-Faire which encourages several employees to always provide new innovations to the government of the governor of West Sumatra and provides opportunities for employees to carry out their duties creatively and innovatively. However, there are also employees who have negative perceptions of the Governor's leadership style. They consider the Governor to have a Laissez-Faire leadership style in which the leadership applied by the governor of West Sumatra tends to be passive. Based on the results of this study, it appears that employee perceptions of the leadership style of the Governor of West Sumatra tend to be stagnant. Factors such as work experience, level of interaction with the Governor, and personal views can influence these perceptions. Therefore, it is important for the Governor and related parties to continue to pay attention to employee perceptions and participate in all activities carried out by employees. This study uses a qualitative approach by conducting in-depth interviews with a number of employees within the West Sumatra provincial government.